Optimizing the Use of Hidram Pump to Supply Water Needs In Nagari Barulak Tanah Datar - Hendri Nurdin; Waskito Waskito; Hasanuddin Hasanuddin; Delima Yanti Sari (Jurnal Aplikasi IPTEK Indonesia, 2020)
Water is one of the financial needs for life. In everyday life we can see the importance of water for all living things, as well as human beings who also need water very much. In Jorong Dalam Nagari Barulak Tanah Datar, the need for clean water is difficult to obtain. This is because the position of this area is in the highlands. During the summer in the highlands it is very difficult to find a source of clean water, so that to meet these water needs, people get it by buying. The solution to overcome this problem is to apply science and technology in the form of a hydram pump that utilizes water pressure from a reservoir from a spring. Then the water is pumped through a pipeline to the divider tank at an elevated area. Clean water supply using a hydram pump is able to distribute water by 18.43 liters/min. So that the performance of a hydram pump continuously (within 24 hours) can supply of water as much as 26.54 m3/day. Applying appropriate technology in the form of a hydram pump as an effort to optimize the supply of clean water from the lowlands to the highlands so that it can address the water needs in the Nagari Barulak community. Utilizing the potential of existing water resources has an impact on increasing activities and reducing public funding for buying clean water.